Update on complications and their management during transradial cardiac catheterization. (3rd October 2019) - Aoun, Joe; Hattar, Laith; Dgayli, Khabib; Wong, Gordon; Bhat, Tariq
ABSTRACT: Introduction : Transradial artery access (TRA) was introduced in 1989 and has been universally used as an alternative approach to the traditional transfemoral access (TFA). Complications of TRA include asymptomatic and less likely symptomatic radial artery occlusion, nonocclusive radial artery injury, radial artery spasm, radial arterial perforation, radial artery pseudoaneurysm, arteriovenous fistula, granuloma formation, access-site bleeding, nerve damage, complex regional pain syndrome along with other rare complications. Areas covered : A literature search was performed using MedLine, PubMed, and Google Scholar (dating to 1 May 2019). Authors reviewed all articles related to transradial artery catheterization, its complications, as well as novel techniques for their management. The article provides insight on the incidence, risk factors, and prevention of such complications along with a description of usual and newer techniques to decrease morbidity. Expert opinion : With increasing experience, TRA complication rate is decreasing and new very uncommon complications are being described. A 'radial first' approach should be implemented in all catheterization laboratories and a physician's familiarity with minor and major complications is a must. Distal radial artery access through the snuff box might be the preferred site of accessing the radial artery and further studies will be needed to prove its superiority to the current access site.